Cytotoxic triterpenoids from Chisocheton pentandrus. (July 2021) - Salam, Supriatno; Harneti, Desi; Maharani, Rani; Nurlelasari,; Safari, Agus; Hidayat, Ace Tatang; Lesmana, Ronny; Nafiah, Mohamad Azlan; Supratman, Unang; Kyle Prescott, Thomas Alexander; Shiono, Yoshihito
Abstract: Eleven undescribed triterpenoids (pentandrucines A to K) were isolated from the n -hexane extract of the stem bark of Chisocheton pentandrus (Blanco) Merr. These comprised ten undescribed dammarane-type triterpenoids and one undescribed apotirucallane-type triterpenoid. Additionally, two dammarane-type triterpenoids, four apotirucallane-type triterpenoids and two tirucallane-type triterpenoids were also isolated. The chemical structures of pentandrucine A-K, were fully elucidated using 1D and 2D-NMR, and high resolution MS. All of the compounds were evaluated for cytotoxic activity against MCF-7 breast cancer cells in vitro. Melianodiol proved to be the most active with an IC50 of 16.84 μM comparing favourably with Cisplatin (13.2 μM). Graphical abstract: Image 1 Highlights: Eleven undescribed triterpenoids were isolated from Chisocheton pentandrus. Their structures were elucidated by 1D, 2D-NMR and high resolution MS. All of the compounds were evaluated for cytotoxic activity against MCF-7 breast cancer cells in vitro. Melianodiol proved to be the most active with an IC50 value of 16.84 μM.